Multiplicityof solution for a singular problem involving the $ φ $-Hilfer derivative and variable exponents - Wafa M. Shammakh; Raghad D. Alqarni; Hadeel Z. Alzumi; Abdeljabbar Ghanmi (AIMS Mathematics)
This paper dealt with the existence of multiple solutions for some singular $ p(s) $-Laplacian problems involving the $ φ $-Hilfer derivative. Precisely, we combined the variational method with the Nehari manifold to prove that such a problem admited two nontrivial solutions. An example was presented to illustrate the effectiveness of our main result.